A GIS-based multi-hazard assessment at the San Pedro volcano, Central Andes, northern Chile - Alcozer-Vargas, Nicolás; Reyes-Hardy, María-Paz; Esquivel, Alfredo; Aguilera, Felipe (Frontiers in Earth Science, 2022)
Recent advances in the computational modeling of volcanic phenomena have allowed scientists to better understand the aleatoric variability coming from the stochastic behavior of volcanic systems. A recurrent first-order parameter is the size (or proportion) of a given phenomenon, commonly represented by the volume/mass parameters. Model-based multi-hazard assessments are based on the first-order parameters to forecast the likelihood of hazard distribution at a given geographic location. However, few multi-hazard assessments consider the size of the eruption (e.g., tephra fallout) to co-parameterize the size of the accompanying phenomena (e.g., mass flows) in the same eruptive scenario. Besides, few studies simulate multi-phenomenon eruptive scenarios with semi-continuous variations in their size, something that allows a better quantification of the aleatoric variability of the volcanic system. Here we present a multi-hazard assessment of the San Pedro volcano, a high-threat volcano from northern Chile, that produced two large-size Plinian eruptions (VEI 5 and 6) in the last 16 ka, and ten Strombolian eruptions (VEI 2) in the last 152 years. The last eruption occurred more than 60 years ago, on 2 December 1960 CE. Here we propose the use of intra-scenarios (i.e., subdivisions of the erupted scenarios) to explore the intra-size variability of various volcanic phenomena. The size of intra-scenarios is extrapolated from the largest-size deposits of each type of phenomenon from the geologic record of the volcano. We simulate explosive scenarios for tephra fallout, concentrated PDCs, and lahars, and effusive scenarios for blocky lava flows. On the local scale, mass flows are likely (33–100%) to affect transport and energy infrastructure up to a 14 km radius. On the regional scale, even though large-size rainy season eruptions are about as likely as not (33–66%) to accumulate 1 cm of tephra on energy, transport, and mining infrastructure up to a 50 km radius from the volcano, these are unlikely (10–33%) to accumulate 1 cm of tephra on the populated city of Calama. This work shows how multi-phenomenon intra-scenarios can be applied to better quantify both phenomena-type and phenomena-size aleatoric uncertainties in volcanic hazard assessments.